1989
DOI: 10.1111/j.1365-2125.1989.tb03562.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration‐response relationships for salicylate‐induced ototoxicity in normal volunteers.

Abstract: 1 Ototoxicity is a common and troublesome side-effect of high-dose aspirin treatment but there has been little previous study of the relationships between the degree of ototoxicity and the plasma concentrations of salicylate. 2 In order to investigate the relationships between aspirin dose, total and unbound plasma salicylate concentrations and ototoxicity, eight normal volunteers were dosed with aspirin 1.95, 3.25, 4.55 and 5.85 g day-1 for 1 week at each dose level, the doses being administered in random ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 8 publications
1
43
0
2
Order By: Relevance
“…However, other studies have suggested that the treatment benefits of aspirin are increased at higher doses. Typically, the plasma salicylate concentrations in humans treated with high doses of aspirin (30-90 mg/kg) are 1-3 mM, which is moderately relevant to the pharmacological levels obtained in clinical practice (Day et al, 1989;Hundal et al, 2002;Hawley et al, 2012). However, it is difficult to equate the cells were treated with resveratrol or AICAR for 6 hours, and SIRT1 enzyme activity was measured.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have suggested that the treatment benefits of aspirin are increased at higher doses. Typically, the plasma salicylate concentrations in humans treated with high doses of aspirin (30-90 mg/kg) are 1-3 mM, which is moderately relevant to the pharmacological levels obtained in clinical practice (Day et al, 1989;Hundal et al, 2002;Hawley et al, 2012). However, it is difficult to equate the cells were treated with resveratrol or AICAR for 6 hours, and SIRT1 enzyme activity was measured.…”
Section: Discussionmentioning
confidence: 99%
“…Salicylate, a widely used anti-inflammatory drug, has been shown to induce tinnitus [5,6,7,8,36,37,38]. In this work, we performed experiments with salicylate at a concentration of 350 mg/kg based on the literature [4,39,40,41,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Natriumsalicylicum (salicylate), the active component of aspirin, is widely used for its antipyretic, analgesic and anti-inflammatory effects. It has been revealed that salicylate can induce reversible tinnitus in both humans and animals [4,5,6,7,8,9,10,11]. Therefore, salicylate is commonly utilized to induce tinnitus in animal models for studies of tinnitus, and salicylate-induced tinnitus could be detected by the conditioned suppression/avoidance procedure [11].…”
Section: Introductionmentioning
confidence: 99%
“…Salicylates reduce pain and fever by inhibiting cyclooxygenase, an enzyme responsible for producing prostaglandins which mediate inflammation and thermoregulation (Vane and Botting 1998). Over this century, there have been numerous reports showing salicylate-induced tinnitus and reversible sensorineural hearing loss (Day et al 1989;Guitton et al 2003;Halla and Hardin 1988;Halla et al 1991).…”
Section: Salicylatesmentioning
confidence: 98%